Proposed Marketing Strategy for Bandung Ciskek (The Indonesian Journal of Business Administration, 2021)
MSME in Indonesia have a very large and crucial contribution to the national economy. Bandung Ciskek is one of the culinary MSMEs from Bandung that sells Japanese Cheese Cake as its main product. As one of the MSME in Bandung, Bandung Ciskek has faced several business issues. The business issue they are currently facing is decline in sales. Therefore, this research is needed which aims to help Bandung Ciskek formulate a marketing strategy to increase their brand awareness. This research using quantitative methods. The first phase in this research is to identify the business issue that is currently faced by Bandung Ciskek. The second phase is to do a business analysis. Business analysis is done through two approaches, external analysis, and internal analysis. The internal analysis consists of STP Analysis and Marketing Mix Analysis. The external analysis consists of, PEST Analysis, Porter's Five Forces Analysis, Customer Analysis, and Competitor Analysis. These solutions focus on maximizing promotional strategies in order to increase brand awareness of Bandung Ciskek, including social media optimization, registering a business location on google my business, implement a new direct marketing strategy, and endorsement using a food blogger. Keywords: Marketing strategy, culinary industry, MSME, brand awareness